1978
DOI: 10.1111/j.1432-1033.1978.tb12040.x
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Lipid Exchange Protein from Rat Hepatoma

Abstract: The postmicrosomal protein fraction from rat hepatoma 27 adjusted to pH 5.1 stimulates phospholipid exchange between rat liver microsomes and mitochondria with higher rates and in a less specific way than the corresponding fraction from rat liver. A phospholipid exchange protein has been purified to homogeneity from the hepatoma pH-5.1 supernatant by gel filtration on Sephadex (3-75 and ion-exchange chromatography on carboxymethylcellulose. The isolated protein had a molecular weight of 1 1 200 as determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The role of these proteins in the intact cell, however, remains obscure. The activity of these proteins is elevated in neoplastic tissue and normal tissues, with elevated lipid translocation requirements suggesting that their activity changes with changing growth state and the need for new membrane synthesis (25)(26)(27)(28). Other investigators have, however, observed discrepancies between the activities observed for the proteins in vitro and events that occur in the intact cell (8,29).…”
Section: Discussionmentioning
confidence: 99%
“…The role of these proteins in the intact cell, however, remains obscure. The activity of these proteins is elevated in neoplastic tissue and normal tissues, with elevated lipid translocation requirements suggesting that their activity changes with changing growth state and the need for new membrane synthesis (25)(26)(27)(28). Other investigators have, however, observed discrepancies between the activities observed for the proteins in vitro and events that occur in the intact cell (8,29).…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid analysis was performed on a TSM amino acid analyzer by the method of Spackman et al [20]. The peptide samples (3)(4)(5) nmol) were hydrolyzed in 0.2 ml of 6 M HCl for 20 h at 110 "C. Amino acid sequence was determined by manual Edman degradation according to the method of Tarr [21]. Automated Edman degradation on the total protease peptide was performed in a Beckman Protein Peptide Sequencer (model 890) using the Quadrol Program.…”
Section: Identification and Sequence Determinationmentioning
confidence: 99%
“…This research has led to our detailed understanding of the extracellular trafficking of sterols by lipoproteins and of lipoprotein uptake by receptor-mediated endocytosis 16. This research has led to our detailed understanding of the extracellular trafficking of sterols by lipoproteins and of lipoprotein uptake by receptor-mediated endocytosis 16.…”
Section: Introductionmentioning
confidence: 99%